Association between enterovirus infection and speech and language impairments: A nationwide population-based study. (June 2018) - Hung, Tai-Hsin; Chen, Vincent Chin-Hung; Yang, Yao-Hsu; Tsai, Ching-Shu; Lu, Mong-Liang; McIntyre, Roger S.; Lee, Yena; Huang, Kuo-You
Abstract: Background and aims: Delay and impairment in Speech and language are common developmental problems in younger populations. Hitherto, there has been minimal study of the association between common childhood infections (e.g. enterovirus [EV]) and speech and language. The impetus for evaluating this association is provided by evidence linking inflammation to neurodevelopmental disorders. Herein we sought to determine whether an association exists between EV infection and subsequent diagnoses of speech and language impairments in a nationwide population-based sample in Taiwan. Methods: Our study acquired data from the Taiwan National Health Insurance Research Database. The sample was comprised of individuals under 18 years of age with newly diagnosed EV infection during the period from January 1998 to December 2011. 39669 eligible cases were compared to matched controls and assessed during the study period for incident cases of speech and language impairments. Cox regression analyses were applied, adjusting for sex, age and other physical and mental problems. Results: In the fully adjusted Cox regression model for hazard ratios, EV infection as positively associated with speech and language impairments (HR = 1.14, 95% CI: 1.06–1.22) after adjusting for age, sex and other confounds. Compared to the control group, the hazard ratio for speech and language impairments was 1.12 (95% CI: 1.03–1.21) amongst the group of EV infection without hospitalization, and 1.26 (95% CI: 1.10–1.45) amongst the group of EV infection with hospitalization. Conclusions: EV infection is temporally associated with incident speech and language impairments. Our findings herein provide rationale for educating families that EV infection may be associated with subsequent speech and language problems in susceptible individuals and that monitoring for such a presentation would be warranted. What this paper adds?: Speech and language impairments associated with central nervous system infections have been reported in the literature. EV are medically important human pathogens and associated with select neuropsychiatric diseases. Notwithstanding, relatively few reports have mentioned the effects of EV infection on speech and language problems. Our study used a nationwide longitudinal dataset and identified that children with EV infection have a greater risk for speech and language impairments as compared with control group. Infected children combined other comorbidities or risk factors might have greater possibility to develop speech problems. Clinicians should be vigilant for the onset of language developmental abnormalities of preschool children with EV infection.